Money Supply and Economic Growth in Sri Lanka (An Empirical Re-Examination of the Monetarist Concept) - Aslam, A.L. Mohamed; Lebbe, S.M. Ahamed; Nisthar, S. (University of Colombo, 2015)
The purpose of this study was to empirically re-examine the causal relationship between money supply and economic growth in Sri Lanka. The time series data used in this study were collected from the sample period from 1959 to 2013. An Augmented Dickey Fuller (ADF) test was used for verifying the unit (stationary) root of the time series variables such as money supply and economic growth, and then a simple regression model was employed in this study to test the long-term relationship between the variables. Based on the regression result, the coefficient of money supply was positive. Therefore, there is a direct relationship between money supply and the Gross Domestic Product (GDP).
Keywords: Money supply, Economic growth, Co-integration, Error Correction Mechanism, Augmented Dickey Fuller test